LEVEL SOFT SEMIRING FROM FUZZY SUBSEMIRING - Saman Abdurrahman; Thresye Thresye (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2026)
This paper introduces the concept of a level soft set and a level soft semiring over a semiring derived from a fuzzy subsemiring. By employing the level subset approach of fuzzy sets, we construct soft structures whose images form subsemirings of the underlying semiring. Several fundamental properties of level soft semirings are established, including their behavior under intersection, union, and AND operations. These results extend classical semiring theory into the fuzzy–soft framework and provide a rigorous algebraic foundation for further theoretical developments. The proposed framework may serve as a basis for future applications in information systems, decision-making, and computational algebra.